Respon Pertumbuhan Awal 2 Varietas Tebu pada Berbagai Penambahan Dosis Mikoriza - Fitrah Ramadhani Firmansyah; Setiyono Setiyono; Distiana Wulanjari; Ayu Puspita Arum; Muhammad Ghufron Rosyady; Oria Alit Farisi (Vegetalika, 2026)
The increasing demand for sugar is not accompanied by increased productivity of sugarcane, the primary raw material for making sugar. Utilizing dry land is one strategy to increase sugarcane productivity. Poor soil fertility caused by limited water and nutrients can affect the growth and productivity of sugarcane. It can be solved by using inorganic fertilizers combined with biological fertilizers such as Arbuscular Mycorrhiza in the planting media. One effort to increase the productivity of sugar cane plants is to improve the quality of sugarcane seedlings. The speed of growth at the beginning of the seeding period is determined by soil fertility and the variety of sugarcane plants used. This research was conducted from September to December 2023 at the Patrang Greenhouse, Jember Regency. This experiment was conducted using Factorial Completely Randomized Factorial Design (CRD) 2 factors with five replications. Factor 1 is the administration of mycorrhizal doses consisting of 4 levels, namely: Aₒ (0 grams), A₁ (5 grams), A₂ (10 grams), A₃ (15 grams). Factor 2 is the variety consisting of 2 types, namely, as follows: V₁ (Bulawang variety) and V₂ (PS 862 variety). The interaction of mycorrhizal dose treatment and the sugarcane variety significantly affected the plant's variable fresh weight. The combination treatment with a mycorrhizal dose of 15 grams applied to the PS 862 (A3V2) sugarcane variety gave the best results.